2014
DOI: 10.1353/pla.2014.0002
|View full text |Cite
|
Sign up to set email alerts
|

Science Instruction Through the Visual Arts in Special Collections

Abstract: The University of Colorado Boulder (CU-Boulder) is known for strong programming in the sciences and a teaching faculty at the forefront of science education and reform. Librarians at CU-Boulder, in collaboration with science faculty, are challenged to improve undergraduate science education. Using rare, historic, and artistic works from Special Collections, the librarians employ active learning techniques that emphasize visual imagery to improve the quality of undergraduate learning in the sciences. This paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Other recent examples of undergraduate student engagement with archives further break away from the perception that these experiences are only useful for traditional history or related humanities courses. In one case, the students of a Microbial Genetics and Physiology course worked with an archivist to examine and analyze historical materials and rare books that documented the historical progress in understanding and documenting diseases (Brown, Losoff and Hollis, 2014). Other instructors have even devised ways to teach abstract mathematical principles and computer science through historical primary sources (Barnett, Lodder, Pengelley, Pivkina and Ranjan, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other recent examples of undergraduate student engagement with archives further break away from the perception that these experiences are only useful for traditional history or related humanities courses. In one case, the students of a Microbial Genetics and Physiology course worked with an archivist to examine and analyze historical materials and rare books that documented the historical progress in understanding and documenting diseases (Brown, Losoff and Hollis, 2014). Other instructors have even devised ways to teach abstract mathematical principles and computer science through historical primary sources (Barnett, Lodder, Pengelley, Pivkina and Ranjan, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Such training, further, is usually carried out with the aim of developing students' abilities to generate new HPS scholarship. However, recent pedagogical research (Sharron and Cotton 2011;Morgan and Yakel 2013;Brown, Losoff, and Hollis 2014;Beam and Schwier 2018;Gray 2020) has shown that archives can offer access to learning activities that combine (a) information literacy with (b) critical thinking while (c) placing students in unique settings that can raise the stakes of their engagement. Developing skills (a) and (b) is especially important for science students, and these are often the sorts of competencies that lead science students to seek out HPS instruction.…”
Section: Introductionmentioning
confidence: 99%
“…45 ics) students in special collections and provide background information on this pedagogical approach. 46 Tresa Randall describes active learning projects she uses to teach dance history with primary sources. 47 Passoneau and Christian employ active learning techniques in their qualitative study on archival education and outreach to sororities and fraternities.…”
Section: Constructivist Learning Theory In Academic Libraries Archivmentioning
confidence: 99%
“…Special collections stimulate active learning. Having special collections of visual material is relevant to student training in collections related to science, technology, engineering, and mathematics (STEM) (Brown, Losoff, and Hollis 2014). Thus, it is an essential rights managements practice to provide access to special collections.…”
Section: Dataset Rights Management and Research Usesmentioning
confidence: 99%